Teacher Perception towards Teacher Smoking Behavior in School among Junior High School Teachers in Bantul District - , RINA MEYLIA YONDA, dr. Prima Dhewi Ratrikaningtyas ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Eventhough people understand about the danger of smoking, the smoking behavior does not decrease and still considered as tolerated behavior by the community and teacher is one of the many people that means special (significant others) for student. Significant others are considered important, expected approval, those who do not want to let down by his students. Objective: The aim of this study is to describe the teacher perception toward teacher smoking behavior in school among junior high school teachers Method: This research is mainly an analytical study which uses cross-sectional study design. Result: The total of 367 respondents whose school environment is positive, 87.7% has good perception